Some Factors Affecting The Stability Of Rutin In Buffered Aqueous Extract Of The Plant Alhagi Graecorum - Marie, N. K.; Al-Khateeb, E.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The flavonoid rutin is the main content of the a queous extract of the Iraqi plant Alhagi graecorum (family Leguminosae) which was given to patients with different dental diseases and gave successful results In this investigation , the amount of rutin is determined and was found to be 4mg/100gm of the dried plant and it is equivalent to 4mg/500ml (0.8mg/100ml) of the mouthwash formula which was prepared in this study This study reported for the first time the expiration date of rutin in the prepared formula and was found to be 2.1 years. It also reported for the first time that the ionic strength, buffer type and buffer concentration had no effect on the hydrolysis of rutin. Photochemical decomposition of rutin was also reported with an expiration date of 4 months. There was also no significant decrease in the concentration of rutin when kept in a plastic container (where the concentration of rutin be 0.79 mg/100 ml), however, the glass container is recommended The results indicated that the Iraqi plant can be used to prepare an effective and stable mouthwash with a low cost since the plant is widely distributed all over the country